Refleksi Pesan Kesehatan Mental Dalam Lagu “Satu Kali” Karya Tulus: Analisis Wacana Kritis - Raudha, Farhania Amama; Abrian, Rizky (GERAM: Gerakan Aktif Menulis, 2023)
This research aims to analyze the song "Satu Kali" by Tulus using discourse analysis methods to understand messages related to mental health in the lyrics. The method used is a qualitative approach with a note-taking approach. In this study, researchers analyzed the lyrics of the song "Satu Kali" in depth, focusing on verses related to mental health. A note-taking approach is used to note down and understand the meaning contained in the lyrics. Researchers looked for the messages that Tulus wanted to convey and analyzed how the lyrics could provide an in-depth understanding of maintaining mental health. The research results show that the song "Satu Kali" by Tulus succeeded in conveying mental health messages well through its lyrics. In the six verses analyzed, the lyrics of this song contain important messages about overcoming life's stresses, self-acceptance, and maintaining emotional balance.